Activity Enhancement of P25 Titanium Dioxide by Zinc Oxide for Photocatalytic Phenol Degradation - Yehezkiel Steven Kurniawan; Leny Yuliati (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
As a benchmark photocatalyst, P25 titanium dioxide (TiO2) nanomaterial has been widely reported for its remarkable photocatalytic activity under ultraviolet (UV) irradiation. However, approaches to further improve the photocatalytic activity of the P25 TiO2 are still required. In the present work, we reported the activity enhancement of the P25 TiO2 up to more than five times higher rate constant for phenol degradation when the P25 TiO2 was coupled with zinc oxide (ZnO). The composites were prepared by a physical mixing method of P25 TiO2 and ZnO with various weight ratios of 1:0.5, 1:1, and 1:2. The composite materials were then characterized using X-ray diffraction (XRD), diffuse-reflectance ultraviolet-visible (DR UV-vis), Fourier transform infrared (FTIR), and fluorescence spectroscopies. All the composites gave better activity than the P25 TiO2, in which the TiO2/ZnO 1:1 composite material exhibited the highest first-order reaction rate constant (0.43 h−1). This remarkable enhanced degradation rate was much higher than that of the unmodified TiO2 (0.08 h−1) and ZnO (0.13 h-1). The fluorescence study revealed that the electron-hole recombination on the P25 TiO2 could be suppressed by the ZnO, which would be the reason for such activity enhancement. A study on the effect of the scavenger showed that the hydroxyl radicals played a crucial role in the photocatalytic phenol degradation. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).